ASAS PUBLISITAS PADA PELAKSANAAN PROGRAM NASIONAL AGRARIA DALAM RANGKA MEWUJUDKAN EFEKTIVITAS PELAYANAN PUBLIK - Rahmat Wiwin Hisbullah (Madani Legal Review, 2019)
PRONA is a series of activities of massive land certification, in a village administration area or other title or parts thereof. Currently, the implementation of PRONA in Indonesia is implemented based on Regulation of the Minister of Agrarian Affairs and Spatial / National Land Agency Number 4 Year 2015 on the National Agrarian Program (hereinafter referred to ATR Regulation of PRONA). Implementation of PRONA is the responsibility of the State so that its implementation is charged to the State Civil Apparatus working in the District Land Office. Thus, the implementation of PRONA is also closely related to government action. In addition to government action, PRONA is also related to public services. Therefore, it is necessary to pay attention to the principles in the administration of land registration, public administration and public services